2008
DOI: 10.1007/s12098-008-0242-z
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac enzyme levels in myocardial dysfunction in newborns with perinatal asphyxia

Abstract: C-Tropopnin assay is useful in evaluating the severity of myocardial damage and outcome in perinatal asphyxia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
34
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 8 publications
(6 reference statements)
7
34
1
Order By: Relevance
“…11 There was a linear relation between the severity of asphyxia as assessed by HIE grading and the CK-MB values. The Percentage of babies with grade three HIE was similar to Rajkumar PS et al, Karnik E et al whereas HIE grade 3 was higher in Jyoti et al 10,12,13 In present study, there was no significant difference in CK-MB values between HIE 1 and 2, whereas between HIE 1 and 3 the rise was statistically significant showing that evaluation of enzymes can be a good tool to assess the severity of HIE. In a study conducted by Merchant S et al also there was a significant difference between HIE1 and 3 ( Table 8).…”
Section: Asphyxia and Hiesupporting
confidence: 83%
See 2 more Smart Citations
“…11 There was a linear relation between the severity of asphyxia as assessed by HIE grading and the CK-MB values. The Percentage of babies with grade three HIE was similar to Rajkumar PS et al, Karnik E et al whereas HIE grade 3 was higher in Jyoti et al 10,12,13 In present study, there was no significant difference in CK-MB values between HIE 1 and 2, whereas between HIE 1 and 3 the rise was statistically significant showing that evaluation of enzymes can be a good tool to assess the severity of HIE. In a study conducted by Merchant S et al also there was a significant difference between HIE1 and 3 ( Table 8).…”
Section: Asphyxia and Hiesupporting
confidence: 83%
“…The ECG changes observed in asphyxiated babies is similar to those observed in Rajkumar PS et al, except that in their study, Grade 2 changes were more. 10 As per Rowe classification Grade 1 and 2 changes are equivocal or suggestive, which is less significant. In Jyoti et al, the ECG changes were classified based on Jedikien classification and Grade 1 changes which are nonspecific.…”
Section: Ecg Changesmentioning
confidence: 98%
See 1 more Smart Citation
“…The predominant features of cardiac dysfunction were respiratory distress (53.3%), shock (48.3%) and congestive heart failure 9 (1.7%) in our study. Rajakumar et al 4 found respiratory distress (66.7%), cardiac failure (36.7%) and cardiogenic shock in 5 (16.7%) neonates in their study. The proportion of neonates having shock in our study is comparable with the fi nding of Mandal et al (44%) 15 .…”
Section: Discussionmentioning
confidence: 61%
“…Perinatal asphyxia is a common problem with the incidence varying from 0.5 -2% of live births [1][2][3][4] . It is an important cause of neonatal mortality and is a frequent cause for admission to neonatal intensive care units (NICU).…”
Section: Introductionmentioning
confidence: 99%